2021
DOI: 10.1128/msphere.01261-20
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Atopobium vaginae at Midtrimester: a Potential Indicator of Preterm Birth Risk in a Nigerian Cohort

Abstract: Preterm birth (PTB) is the largest contributor to infant death in sub-Saharan Africa and globally. With a global estimate of 773,600, Nigeria has the third highest rate of PTB worldwide. There have been a number of microbiome profiling studies to identify vaginal microbiomes suggestive of preterm and healthy birth outcome. However, studies on the pregnancy vaginal microbiome in Africa are sparse with none performed in Nigeria. Moreover, few studies have considered the concurrent impact of steroid hormones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…Aromatic amino acid biosynthesis, carbohydrate degradation, pentose phosphate pathway that may cause preterm birth were enriched in asymptomatic BV women. Women who gave preterm birth had a vaginal microbiome enriched with the nonoxidative branch of the pentose phosphate pathway ( Odogwu et al., 2021 ). Thus, functionally, many of the enriched BV pathways were also reflective of vaginal microbiota associated with preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic amino acid biosynthesis, carbohydrate degradation, pentose phosphate pathway that may cause preterm birth were enriched in asymptomatic BV women. Women who gave preterm birth had a vaginal microbiome enriched with the nonoxidative branch of the pentose phosphate pathway ( Odogwu et al., 2021 ). Thus, functionally, many of the enriched BV pathways were also reflective of vaginal microbiota associated with preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive Tract Infections (RTIs) caused by bacteria, viruses or protozoa have a profound impact on the reproductive and sexual health of men and women. The consequences of sexually transmitted infections/reproductive Tract Infections (STIs/RTIs) for reproductive health include pelvic inflammatory disease (PID), infertility (in women and men), ectopic pregnancy, and adverse pregnancy outcomes including miscarriage, stillbirth, preterm birth, and congenital infection ( Mullick et al., 2005 ; Odogwu et al., 2021 ). STIs and RTIs are also known to increase the risk of HIV transmission ( Taha and Gray, 2000 ; van de Wijgert et al., 2008 ; Ward and Rönn, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…in the vaginal microbiota delivered preterm as also reported in previous studies 7 , 22 , 58 , 59 . In particular, Atopobium (CST IV) remained persistent throughout pregnancy in women who delivered preterm, buttressing a cause-effect relationship between Atopobium and preterm birth 7 , 60 62 . Our data further reveal that the vaginal microbiome of Nigerian women was typically dominated by L. iners .…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Atopobium are commonly found in the vaginas of women, with 97% of these being A. vaginae ( 30 ), a Gram-positive, strict anaerobe that produces major amounts of lactic acid ( 31 ). This kind of bacteria has been considered a common component of the vaginal microbiome, but a series of studies found that Atopobium in the female genital tract is associated with different female reproductive disorders; for example, an A. vaginae – dominated vagitype was observed in pregnant women who delivered preterm babies in a Nigerian cohort ( 32 ), and women at high risk of preterm birth were identifiable by a high vaginal load of A. vaginae (DNA level ≥ 108 copies/mL) ( 33 ). Second, previous study has suggested Atopobium to be one of the significantly more abundant genera associated with recurrent spontaneous abortion ( 34 ).…”
Section: Discussionmentioning
confidence: 99%